Electronic troubleshooting - Tomal, Daniel R.; Agajanian, Aram S. (New York : McGraw-Hill Education, 2014)
The book uniquely blends traditional electrical theory and components with modern networking and electronic technology. Chapter-ending questions and problems test your understanding of the topics discussed. Filled with tables, charts, illustrations, graphs, and flowcharts, this is a must-have manual for anyone who works with electronics--at home or on the job. --Publisher's description.
Chapter 1. Principles of troubleshooting -- Chapter 2. Electronics test instruments -- Chapter 3. Troubleshooting electric motors and generators -- Chapter 4. Troubleshooting industrial controls -- Chapter 5. Troubleshooting residential, commercial, and wireless communication systems -- Chapter 6. Troubleshooting radio and television -- Chapter 7. Troubleshooting digital circuits -- Chapter 8. Troubleshooting combinational and sequential digital circuits -- Chapter 9. Troubleshooting microprocessor-based systems -- Chapter 10. Troubleshooting biomedical equipment -- Chapter 11. Computer networking and network devices -- Chapter 12. Troubleshooting embedded microprocessor systems.
Includes index.
Keywords: Electronic apparatus and appliances -- Maintenance and repair; Electric apparatus and appliances -- Maintenance and repair